A Longitudinal Cluster-Randomized Controlled Study on the Accumulating Effects of Individualized Literacy Instruction on Students’ Reading From First Through Third Grade - Connor, Carol McDonald; Morrison, Frederick J.; Fishman, Barry; Crowe, Elizabeth C.; Al Otaiba, Stephanie; Schatschneider, Christopher (Psychological Science, 2013)
Using a longitudinal cluster-randomized controlled design, we examined whether students’ reading outcomes differed when they received 1, 2, or 3 years of individualized reading instruction from first through third grade, compared with a treated control group. More than 45% of students came from families living in poverty. Following students, we randomly assigned their teachers each year to deliver individualized reading instruction or a treated control condition intervention focused on mathematics. Students who received individualized reading instruction in all three grades showed the strongest reading skills by the end of third grade compared with those who received fewer years of such instruction. There was inconsistent evidence supporting a sustained first-grade treatment effect: Individualized instruction in first grade was necessary but not sufficient for stronger third-grade reading outcomes. These effects were achieved by regular classroom teachers who received professional development, which indicates that policies that support the use of evidence-based reading instruction and teacher training can yield increased student achievement.